Investigation of Dye Adsorption on Thermally Activated Adsorbent Derived from Tamarindus Indica Leaves (Journal of Engineering Science, 2025)
In leather processing, dyeing is an essential operation in leather manufacturing to make the final leather attractive. The resulting dyeing effluent poses a significant threat to human health and the aquatic ecosystem. This study examines the feasibility of using thermally activated adsorbent derived from the Tamarindus indica leaves to remove the dye from dyeing effluent. The collected Tamarindus indica leaves were subjected to thermally activated at 350°C for two hours. Before and after use, the adsorbent was characterized through Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FT-IR) spectroscopy. Batch experiments were conducted to evaluate the dye adsorption capacity of the activated adsorbent from tannery dyeing wastewater. For maximum dye removal efficacy, several factors- adsorbent dose, pH, stirring time, and setting time are optimized. The results showed that the highest dye removal efficiency was achieved by the thermally activated Tamarindus indica leaves adsorbent 97.09% with an adsorbent of 0.75 g/25 mL wastewater, pH 4.8, stirring time 30 minutes, coagulant dose 0.3-g/25 mL wastewater, and 20 hours settling time. Moreover, the study reduced turbidity, Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD) levels by 99.62%, 80.38%, and 43.70%, respectively. The research findings suggest that Tamarindus indica leaves-based activated adsorbent is promising for dye removal from tannery wastewater.Journal of Engineering Science 15(2), 2024, 105-112